Pelindungan Hukum terhadap Tari Tor-Tor Sipitu Sawan sebagai Ekspresi Budaya Tradisional Berdasarkan Undang-Undang Nomor 28 Tahun 2014 - Roselli Anjelina Lumbansiantar; Parlaungan Gabriel Siahaan (CV Rewang Rencang, 2025)
The Sipitu Sawan tortor dance is an art that has high cultural value. In the midst of developments, this dance faces challenges related to legal protection. This research aims to analyze the form of legal protection for the Sipitu Sawan tortor dance as expression of traditional culture, the challenges in efforts to provide legal protection for the Sipitu Sawan tortor dance as expression of traditional culture, and analyze the role of the government and indigenous/local communities in maintaining the existence and rights to the Sipitu Sawan tortor dance. Using qualitative descriptive methods and a normative-empirical approach, it was found the implementation of Article 38 of Law no. 28 of 2014 not optimal in the region. Lack of documentation, legal dissemination, risk of cultural claims are the main problems.